Poverty-Inequality-GDP Nexus and Social Grants: Implications for SDGs in South Africa - Kanayo, Ogujiuba; Mngometulu, Ntombifuthi; Agholor, Isaac; Maponya, Lethabo (International Journal of Economics and Financial Issues, 2025)
The policy framework in many emerging economies is based on the triangular concerns of poverty, inequality, and economic growth. In this case, social protection and grants serve as efficient means of providing welfare packages to the public. Nonetheless, South Africa still has one of the most unequal socioeconomic structures in the world, despite the social grant system. This study focuses on the dynamic trend of poverty, inequality, and GDP, which is crucial to the attainment of SDG objectives in South Africa. The instrument of estimation is the ARIMA principle using data spanning 1990 - 2020 for prognosis. The study forecasts that between the present and 2050, poverty and inequality would rise, but more slowly. The policy implication is that a concerted effort through policy re-appraisal and review that will change the nature of rural and township life and allow people to move from a high level of poverty and inequality to a better life-changing status is recommended.